2022
DOI: 10.1017/ice.2022.56
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistent symptoms after severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection among healthcare workers: Results of a multisite survey

Abstract: The coronavirus disease 2019 (COVID-19) pandemic continues, and healthcare workers (HCWs) are at increased risk of infection. 1 In addition to the morbidity associated with initial illness, persistent postviral symptoms, currently classified as postacute sequelae of COVID-19 (PASC), 2 also affect HCWs, causing further disruptions in their work, home, and social lives. 3 To further characterize PASC in this population, who are otherwise expected to be highly functional and in relatively good health, we sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A number of studies showed the association of the severity of the acute COVID-19 with the occurrence of long-term neurological consequences [ 23 , 39 , 42 , 46 , 48 , 49 , 50 ]. It was also found that the number of initial symptoms better predicts the presence of long COVID than the severity of the acute phase of the disease [ 47 , 50 , 56 ]. Other studies showed that severity of the acute phase of the disease is less important as predictor of the long-term health complications than cumulative number of the specific COVID-19 symptoms, so-called number of initial symptoms, during the first week of acute phase [ 47 , 50 , 56 ].…”
Section: Predictors Of Post-covid Neurological Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies showed the association of the severity of the acute COVID-19 with the occurrence of long-term neurological consequences [ 23 , 39 , 42 , 46 , 48 , 49 , 50 ]. It was also found that the number of initial symptoms better predicts the presence of long COVID than the severity of the acute phase of the disease [ 47 , 50 , 56 ]. Other studies showed that severity of the acute phase of the disease is less important as predictor of the long-term health complications than cumulative number of the specific COVID-19 symptoms, so-called number of initial symptoms, during the first week of acute phase [ 47 , 50 , 56 ].…”
Section: Predictors Of Post-covid Neurological Complicationsmentioning
confidence: 99%
“…It was also found that the number of initial symptoms better predicts the presence of long COVID than the severity of the acute phase of the disease [ 47 , 50 , 56 ]. Other studies showed that severity of the acute phase of the disease is less important as predictor of the long-term health complications than cumulative number of the specific COVID-19 symptoms, so-called number of initial symptoms, during the first week of acute phase [ 47 , 50 , 56 ]. Miskowiak et al [ 23 ] studied the relationship between acute phase severity and cognitive changes in post-COVID patients.…”
Section: Predictors Of Post-covid Neurological Complicationsmentioning
confidence: 99%
“…We and others have found significant dose-response relationships between the intensity of COVID-19 related occupational stressors experienced and negative psychiatric and occupational outcomes in healthcare workers, supporting a causal role of stressful and demoralizing experiences for healthcare workers working during the pandemic on psychiatric and occupational outcomes 1,4 . Alternatively, acute infection with COVID-19 has itself been found to be associated with persistent increases in psychiatric distress and worsened functional outcomes in a wide variety of populations 5 , including healthcare workers 6 . As high rates of exposure to COVID-19 related occupational stressors and elevated risk of COVID-19 infection have often gone hand in hand for healthcare workers, it has been challenging to assess the relative contributions of COVID-19 infection and occupational stress and trauma for healthcare worker health and occupational outcomes.…”
Section: Introductionmentioning
confidence: 99%